2004
DOI: 10.1111/j.1349-7006.2004.tb02204.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid induction of skin and mammary tumors in human c‐Ha‐ras proto‐oncogene transgenic rats by treatment with 7,12‐dimethylbenz[a]anthracene followed by 12‐O‐tetradecanoylphorbol 13‐acetate

Abstract: We have established a transgenic rat line carrying 3 copies of the human c-Ha-ras proto-oncogene with its own promoter region (Jcl/SD-TgN(HrasGen)128Ncc) (Hras128 rat), expression being detectable in almost all organs. We have already demonstrated that the rat is highly sensitive to mammary, esophagus and bladder carcinogenesis. In the present study, male and female transgenic and wild-type littermates were topically treated with 2.5 mg of 7,12-dimethylbenz[a]anthracene (DMBA) dissolved in 1.0 ml of acetone on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…These results clearly show that Hras128 rats are more sensitive to 4NQO induced tongue carcinogenesis than SD rats. This susceptibility to a carcinogen is in accordance with previous experiments demonstrating that Hras128 rats are more sensitive to a 7,12-dimethylbenz[a]anthracene (DMBA) or 4NQO in the mammary or tongue tumors than were wild-type SD rats (11,21). In addition, Miyamoto et al demonstrated that the rasH2 mouse carcinogenesis model is highly susceptible to 4NQO induced tongue and esophageal tumors (12).…”
Section: Discussionsupporting
confidence: 77%
“…These results clearly show that Hras128 rats are more sensitive to 4NQO induced tongue carcinogenesis than SD rats. This susceptibility to a carcinogen is in accordance with previous experiments demonstrating that Hras128 rats are more sensitive to a 7,12-dimethylbenz[a]anthracene (DMBA) or 4NQO in the mammary or tongue tumors than were wild-type SD rats (11,21). In addition, Miyamoto et al demonstrated that the rasH2 mouse carcinogenesis model is highly susceptible to 4NQO induced tongue and esophageal tumors (12).…”
Section: Discussionsupporting
confidence: 77%
“…61) In the present study, atrazine and nonylphenol inhibited development of DMBA-induced skin tumors in male Tg rats, in line with earlier data for estradiol. 36) In Tg rats, feminization by endocrine disruptors may thus play a role in reducing the skin tumors, which do not develop in females.…”
Section: Discussionmentioning
confidence: 99%
“…36) We recently showed that the transgenic (Tg) rats have a potential for use in medium-term bioassay models to test for the modifying effects of estrogenic environmental compounds on mammary tumor development. 37) In the present study, they were employed to investigate potential modifying effects of atrazine and nonylphenol on DMBA mammary and skin carcinogenesis.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Mice treated with DEN were monitored up to an end point of 12 mo, after which all animals were euthanized and examined at necropsy for evidence of tumor formation. For skin carcinogenesis, mice were shaved and the dorsal epidermis was treated essentially as described (30,31) with a single dose of 400 nmol 7,12-dimethylbenz(a)anthracene (DMBA) followed by a twice-weekly application of 17 nmol phorbol ester 12-O-tetradecanoylphorbol-13-acetate (TPA). Mice treated with DMBA + TPA were monitored to a 20-wk end point for skin tumors.…”
Section: Methodsmentioning
confidence: 99%